Credit risk, energy gap and institutional investors: An empirical analysis on Pakistani conventional banks - Mehmood, Abid (2020)
The stability of banking sector in Pakistan is relatively weak. Nonperforming loans (NPL) is one of the prime focus among Financial Stability Indicators (FSI). Empirical studies suggested that the factors affecting NPL can broadly be divided into external and internal elements. This study attempted to examine the selected factors from these elements as predictors of NPL for conventional banks. An unbalanced panel of 20 banks over a period of 12 years (2006-2017) with a total of 235 observations were formed. Panel corrected standard errors estimator (PCSE) was used to control the panel data issues. All identified factors were found to have significant influence on NPL. Specifically, energy gap, corruption, political instability as well as bank credit to private sector are the novel contributor to the variability in NPL. Besides, the hierarchical multiple moderated regressions were used to examine the moderating effects of the prevailing management structure in Pakistani banking sector. Based on the result, institutional investors (II) moderates all three internal factors namely capital adequacy ratio (CAR), loan-to-deposit ratio (LTD) and return on assets ratio (ROA). This study recommended that Pakistan should improve ownership structure in the banking sector in order to control the stake of institutional investors. Also, the regulators should devise policies with autonomy and responsibility to control corruption and political interference in lending. Lastly, the Pakistani government needs to ensure a conducive environment in which sufficient electrical energy can be properly supplied. This will facilitate the lending process of the lending sector to the affected sectors and indirectly help boost the country's economic growth.